Outpatient care changes and associated mortality among Veterans with heart failure during the COVID-19 pandemic. - Shilpa Vijayakumar; Emily Corneau; Sebhat Erqou; Aravind Kokkirala; Wen-Chih Wu (PLoS ONE)
Background The mortality risk associated with loss of in-person outpatient visits or transition to virtual care in patients with heart failure (HF) during the COVID-19 pandemic is unknown. Objectives Assess changes in outpatient HF care patterns and associated mortality. Methods Retrospective analysis of HF patients using national Veterans-Health-Administration (VHA) data. Among 509,511 HF patients who received VHA care, we compared mean monthly days-with-an-outpatient-visit from 2/2018-1/2020 (pre-COVID) versus 2/2020-1/2021 (COVID) using T-tests. In a subset of 321,439 patients with ≥1 VHA cardiology or primary-care visit in 2019, we related the presence and type of outpatient visit with mortality using Cox-Regression estimated hazard-ratios (HRs). Results Despite a 2-3-fold increase in video-only visits and use of telephone visits to maintain access, the overall days with outpatient visits decreased from a monthly-average of 81.4 ± 6.1 in 2018-2019 and 81.0 ± 5.6 in 2019-2020, to 57.8 ± 11 days in 2020-2021 (P < 0.01 for both), per 100 Veterans. When compared to patients with no-visits during the study period, the adjusted-mortality risk was lowest for patients with at least one in-person (HR 0.42, 95%CI: 0.41-0.44), followed by video-only (HR 0.52, 95%CI: 0.50-0.55) and then telephone-only (HR 0.57, 95%CI: 0.54-0.60) visits (p = 0.14 for trend). Results remained similar when the analysis was repeated (without including telephone visits) for pre-COVID (2/2018-1/2020) periods. Conclusions Despite an increase in video and use of telephone visits during the COVID-19 pandemic, there was still a decrease in total outpatient visits for patients with HF. The presence and type of outpatient encounter was associated with the adjusted risk of mortality.